The Development of Self-Acceptance in Adolescents (Descriptive Study of Grade XI High School Student in Subang) - Azrina Abharini; Nandang Rusmana; Nandang Budiman (Universitas PGRI Yogyakarta, 2023)
Self-acceptance is a positive attitude towards oneself, awareness and acceptance of various aspects such as the good and bad of oneself as well as past life experiences. A phenomenon that occurs in adolescents, there are still many adolescents who have low self-acceptance, especially high school students. Therefore, this research is aimed to examine self-acceptance in high school adolescents. This research is a quantitative descriptive. Participants in this research were 381 students grade XI. The data using self-acceptance instruments that developed and gone through expert feasibility tests and empirical tests using Rasch model. From the data obtained, that there are 66 students who have high self-acceptance, 259 people in the medium category and 56 people in the low category. The conclusion is that students are not yet fully able to accept themselves regarding the conditions they are experiencing and this can be the basis for implementing services to develop students' self-acceptance. Keywords: self-acceptance, adolescents, development